Natural Factors Contributing to the Development of Supply Chain Management in New Biotechnological Production - A.R. Romanov; R.R. Nogovitsyn; V.E. Borisov (International Journal of Supply Chain Management, 2019)
The goal of the research is the economic evaluation of the competitive biotechnological industry development in the Republic of Sakha (Yakutia) in the context of the influence of natural and climatic factors on living creatures and plants based on the supply chain management.The article is devoted to the extreme climate peculiarities of Yakutia and the competitive advantages of the natural raw materials of plant and animal origin, which can be used in the biotechnological industry to improve the living quality of the population. The authors studied the physio-graphic, natural and climatic characteristics of the region as well as the dependence of its flora and fauna on the habitat conditions. The economic mechanisms of the biotechnological industry development by supply chain management have been defined here.